2021
DOI: 10.3389/fpsyg.2021.665508
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Mental Imagery and Change of Direction Performance in Young Elite Soccer Players of Different Maturity Status

Abstract: Previous studies have not considered the potential influence of maturity status on the relationship between mental imagery and change of direction (CoD) speed in youth soccer. Accordingly, this cross-sectional study examined the association between mental imagery and CoD performance in young elite soccer players of different maturity status. Forty young male soccer players, aged 10-17 years, were assigned into two groups according to their predicted age at peak height velocity (PHV) (Pre-PHV; n = 20 and Post-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Accordingly, several studies have found an association between physical abilities such as strength, speed, and agility performance [ 11 , 19 ]. Sariati et al [ 20 ] recently showed an association between mental imagery and changes in direction in a small sample of young soccer players using the same agility test achieved in the current investigation. Furthermore, morphological changes in the athlete’s body during puberty have been proven to influence muscle mass and muscular strength, such as in vertical jumps and sprints [ 21 ].…”
Section: Introductionsupporting
confidence: 73%
“…Accordingly, several studies have found an association between physical abilities such as strength, speed, and agility performance [ 11 , 19 ]. Sariati et al [ 20 ] recently showed an association between mental imagery and changes in direction in a small sample of young soccer players using the same agility test achieved in the current investigation. Furthermore, morphological changes in the athlete’s body during puberty have been proven to influence muscle mass and muscular strength, such as in vertical jumps and sprints [ 21 ].…”
Section: Introductionsupporting
confidence: 73%
“…The effectiveness of imagery and how athletes use it are influenced by variables such as gender, skill type (open or closed), competitive level (elite vs. non-elite athletes), and types of sports (team sports vs. individual sports; contact vs. non-contact sports) [ 259 ]. Studies have found differing uses and capabilities in imagery among male and female athletes, as well as between elite and non-elite players, in various sports [ 261 , 262 , 263 , 264 , 265 , 266 , 267 , 268 , 269 , 270 , 271 ].…”
Section: Performance Enhancement and Mental Strategiesmentioning
confidence: 99%
“…Coordination is the ability to perform movements with various difficulty levels efficiently, quickly and with full accuracy [8]. Coordination is one of the most important components of physical condition and is needed in almost all sports, especially football.…”
Section: Introductionmentioning
confidence: 99%